3D in vitro platform produced by two-photon polymerization for the analysis of neural network formation and function. (27th April 2016) - Timashev, P S; Vedunova, M V; Guseva, D; Ponimaskin, E; Deiwick, A; Mishchenko, T A; Mitroshina, E V; Koroleva, A V; Pimashkin, A S; Mukhina, I V; Panchenko, V Ya; Chichkov, B N; et al.
Abstract: Zr-Si organic–inorganic scaffolds fabricated by a two-photon polymerization technique were used for the primary culture of mouse embryonic neural cells. We observed that dissociated hippocampal cells adhere to the scaffolds, produce neurites, elongate and differentiate into adult neurons. Neuronal outgrowth and synaptogenesis were confirmed by immunohistochemical staining with antibodies against β III-Tubulin and synaptophysin. The formation of a functional neural network was assessed by the measurement of spontaneous activity using Ca 2+ imaging of dissociated hippocampal cultures grown on Zr-Si scaffolds. The results of this study suggest that two-photon-induced polymerization of organic–inorganic hybrid biomaterials provides a robust model for 3D neuronal tissue engineering studies.